THE EFFECT OF MOTIVATION, SATISFACTION AND WORK DISCIPLINE ON EMPLOYEE PERFORMANCE OF PT. TRIWIRA INSANI LESTARI TBK - Nurjaman NURJAMAN (Journal of Education and Leadership in Education, 2020)
This study aims to determine the effect of motivation, satisfaction and work discipline simultaneously on the performance of employees of PT. Triwira Insani Lestari Tbk, to know the effect of motivation on employee work performance partially, to know the effect of job aging on employee work performance partially and to determine the effect of work discipline on employee performance of the company. The data collected came from 52 employees of PT. Triwira Insani Lestari Tbk. The amount is all of the employees in the company. The data is then analyzed using regression and statistical testing with the F test and t test. Job satisfaction variables partially affect the performance of employees of PT. Triwira Insani Lestari Tbk amounted to 75.0% while the rest was influenced by other variables which were not analyzed or not included in the model. The t value is 12.237 and the significance value is 0.000. This means that the job satisfaction variable has a significant effect on employee performance. Discipline variable partially affects the performance of employees of PT. Triwira Insani Lestari Tbk amounted to 42.5% while the rest was influenced by other variables which were not analyzed or not included in the model. The t value is 6.084 and the significance value is 0.000. This means that the discipline variable has a significant effect on employee performance.